#3**0 **

\(6-(x+5) = 4x \) is the equation and we want to find \(x\).

The minus sign in front of the parentheses means everything inside the parentheses is multiplied by -1.

For example, \(-(4)\) equals \(-1\times 4\), which is also just \(-4\).

However, \(-(-2)\) equals \(-1\times -2\), which is \(2\).

And \(-(3+2)\) can be interpreted as \(-1\times 3-1\times 2\), or \(-5\).

Got it?

Now, \(-(x+5) = -x-5\), so \(6-x-5 = 4x, 1-x=4x, 1 = 5x, x = \frac{1}{5}\).

You are very welcome!

:P

CoolStuffYT Sep 21, 2019